2022
DOI: 10.1007/s00262-022-03214-4
|View full text |Cite
|
Sign up to set email alerts
|

An oral WT1 protein vaccine composed of WT1-anchored, genetically engineered Bifidobacterium longum allows for intestinal immunity in mice with acute myeloid leukemia

Abstract: Wilms’ tumor 1 (WT1) is a promising tumor-associated antigen for cancer immunotherapy. We developed an oral protein vaccine platform composed of WT1-anchored, genetically engineered Bifidobacterium longum (B. longum) and conducted an in vivo study in mice to examine its anticancer activity. Mice were orally treated with phosphate-buffered saline, wild-type B. longum105-A, B. longum 2012 displaying only galacto-N-biose/lacto-N-biose I-binding protein (GLBP), and WT1 protein- and GLBP-expressing B. longum 420. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Among these, we selected WT1 35 as an epitope with the most potent IFN-γ-producing capability of CD4 + T cells that strengthen the CTL-induced WT1-specific lysis of RMAS cells pulsed with WT1 35–52 peptide, suggesting its great potential of inducing CD4 + T cell help that provides critical cellular and molecular mechanisms in CTL responses in cancer immunotherapy [ 12 ]. In addition, Nakagawa et al demonstrated that an oral WT1 protein vaccine of WT1-anchored, genetically engineered B. longum provokes intestinal immunity to exert the cytotoxic activity of WT1-specific CD8 + T cells possibly through CD4 + T cell help [ 16 ]. Results from the present study indicate that the combination of B. longum 420 and B. longum 2656 exhibited the most enhanced anticancer activity in intestinal immunity among studied materials, supporting the reasonable therapeutic strategy of genetically engineering a WT1 amino acid sequence 35–52 into an oral B. longum -based vaccine structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, we selected WT1 35 as an epitope with the most potent IFN-γ-producing capability of CD4 + T cells that strengthen the CTL-induced WT1-specific lysis of RMAS cells pulsed with WT1 35–52 peptide, suggesting its great potential of inducing CD4 + T cell help that provides critical cellular and molecular mechanisms in CTL responses in cancer immunotherapy [ 12 ]. In addition, Nakagawa et al demonstrated that an oral WT1 protein vaccine of WT1-anchored, genetically engineered B. longum provokes intestinal immunity to exert the cytotoxic activity of WT1-specific CD8 + T cells possibly through CD4 + T cell help [ 16 ]. Results from the present study indicate that the combination of B. longum 420 and B. longum 2656 exhibited the most enhanced anticancer activity in intestinal immunity among studied materials, supporting the reasonable therapeutic strategy of genetically engineering a WT1 amino acid sequence 35–52 into an oral B. longum -based vaccine structure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent technologies including flow cytometry and single-cell RNA sequencing provide an unprecedented view of the composition, function, and location of immunocompetent cells within the tumor microenvironment (TME) [ 17 ]. Our data on TILs indicate 1) the increased frequency of WT1-specific CTLs in CD8 + T cells, 2) the obvious production of WT1-specific IFN-γ by CD4 + T cells, and 3) the strengthened tumor-infiltrating capability of WT1-specific CTLs primed in the intestine [ 16 ], all of which afford flow cytometric evidence about the antitumor activity of combining B. longum 420 for WT1-specific CD8 + T cell activation and B. longum 2656 for CD4 + T cell help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental principle of cancer immunotherapy, including ICI, is to induce or activate tumor-speci c cellular immunity. Many studies have been conducted on cancer vaccines that can arti cially induce tumor immunity and can be used in combination with ICI 4,5 . Cancer vaccines, which can forcibly induce tumor-speci c cellular immunity through antigen presentation to dendritic cells, are a promising treatment strategy for enhancing the e cacy of cancer immunotherapy 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on cancer vaccines that can arti cially induce tumor immunity and can be used in combination with ICI 4,5 . Cancer vaccines, which can forcibly induce tumor-speci c cellular immunity through antigen presentation to dendritic cells, are a promising treatment strategy for enhancing the e cacy of cancer immunotherapy 5,6 . The National Cancer Institute has ranked tumor associated antigens (TAA) as targets for cancer vaccines based on criteria such as therapeutic e cacy, immunogenicity, carcinogenicity, speci city, expression level and positive cell rate.…”
Section: Introductionmentioning
confidence: 99%